Editorial - Mujanović, Eldan (Kriminalističke teme, 2014)
Dear reader, It is my great pleasure to introduce to you a new English edition of the Criminal Justice Issues – the Journal of Criminalistics, Criminology and Security Studies. As it has been the practice in previous editions, this one includes a wide range of current issues in the field of criminal investigation science, criminology, security studies and sociology. In this publication, you can find six scientific papers that meet the quality, scientific as well as professional relevance standards completely.. Among those papers, there are two original scientific papers, one preliminary note and three review papers. Original scientific papers refer to the area of criminology and sociology. On the other side, preliminary note refers to area of security studies, while review papers consider issues in the field of security studies, sociology and criminal investigation science/criminology. The original scientific paper titled Police and Persecution in the Bosnian Krajina: Democratisation, Deprofessionalisation and Militarisation examines processes leading to police participation in ethnic violence during the war in the Bosnian Krajina and contributes to a growing body of criminological work using the rich resources provided by the ICTY and other courts dealing with atrocity crime. The next original scienific paper titled Concentration Camp Rituals: An Extreme Case of Insecurity involves sociological analysis of the experiences retold by former civilian detainees who were placed in concentration camps at the beginning of the Bosnian war in the 1990s. Afterward, there is a, followinginteresting paper entitled Security Management and Environmental Crime - Security Management Students’ Attitudes which aims to assess knowledge of students at the University of Belgrade – Faculty of Security about their understanding of environmental crimes. The first of review papers is entitled Terrorism and Genocide whereas the author strives to find the symbiotic relationship and the role of terrorism as supporting instrument in carrying out genocide. The paper titled The Social Functions of Middle Class: Implications for Bosnia and Herzegovina is considering the need of revitalization of the middle class social values and creating an environment where the social habit of middle class will be established as a normative guideline. This edition ends with the paper Trafficking In Human Beings In Bosnia And Herzegovina: State Of The Art And Associated Puzzles wherein the autors research and clarify the phenomenon of trafficking in human beings in Bosnia and Herzegovina, elaborate its history, the state of the art, and the exploitation patterns of trafficking. At the end of this editorial, I would like to express my gratitude to all members of the Editorial Board as well as to Mr. Andy Aitchison, PhD, for their support and efforts given in preparation of this Criminal Justice Issues edition. Especially, I would like to thank the peer reviewers whose work has contributed significantly to improving the quality of this edition.